Change in Extreme Precipitation Over Indochina Under Climate Change From a Lagrangian Perspective of Water Vapor - Cheng, Zelun; Xie, Zuowei; Tang, Wei; Bueh, Cholaw; Gong, Yuanfa; Yan, Jie (Frontiers in Earth Science, 2021)
The process of global warming has humidified the atmosphere and increased the occurrence of extreme precipitation events over the Indochina Peninsula, which lies in the transition region from the South Asian monsoon to the East Asian monsoon. The annual occurrence number of days of extreme precipitation over the Indochina Peninsula exhibits a significant change in 2003, with an abnormally higher occurrence number during the period 2003–2015 than that of 1951–2002. The extreme precipitation and such decadal change are contributed by more moisture sources associated with an enhanced dipole circulation over the Indian Ocean, which could be linked to the Pacific Decadal Oscillation. The daily large-scale meteorological pattern directly associated with extreme precipitation is characterized by an enhanced dipole of the typical summer monsoon pattern, with a zonally elongated Mascarene high and a deepened monsoon trough from northern India to the South China Sea. Such an intensified dipole provides two major channels of water vapor: one along the low-level westerly jet over the Indian Ocean, and the other along the gyre of monsoon trough over the South China Sea. Compared with the period of 1951–2002, the dipole is enhanced from northern India to the Indian Ocean and weakened over the Indochina Peninsula during the period 2003–2015. Although the Lagrangian analysis shows that the trajectory of air masses is displaced southwards to the Indian Ocean, the intensified low-level westerly jet increases the evaporation of water from the ocean and thus not only enhances the water channel over the Indian Ocean but also yields a parallel water channel over the Bay of Bengal. In contrast, in spite of the increased trajectory density of air masses over the South China Sea, the lingering of air masses suppresses the evaporation of water and thus provides a declined contribution to the extreme precipitation during 2003–2015.